Cancer spectrum in TP53-deficient golden Syrian hamsters: A new model for li-fraumeni syndrome - Jinxin Miao (Wolters Kluwer Medknow Publications, 2021)
Background: The TP53 tumor suppressor gene is the most commonly mutated gene in human cancers. Humans who inherit mutant TP53 alleles develop a wide range of early onset cancers, a disorder called Li-Fraumeni Syndrome (LFS). Trp53-deficient mice recapitulate most but not all of the cancer phenotypes observed in TP53-deficient human cancers, indicating that new animal models may complement current mouse models and better inform on human disease development. Materials and Methods: The recent application of CRISPR/Cas9 genetic engineering technology has permitted the emergence of golden Syrian hamsters as genetic models for wide range of diseases, including cancer. Here, the first cancer phenotype of TP53 knockout golden Syrian hamsters is described. Results: Hamsters that are homozygous for TP53 mutations become moribund on average ~ 139 days of age, while hamsters that are heterozygous become moribund at ~ 286 days. TP53 homozygous knockout hamsters develop a wide range of cancers, often synchronous and metastatic to multiple tissues, including lymphomas, several sarcomas, especially hemangiosarcomas, myeloid leukemias and several carcinomas. TP53 heterozygous mutants develop a more restricted tumor spectrum, primarily lymphomas. Conclusions: Overall, hamsters may provide insights into how TP53 deficiency leads to cancer in humans and can become a new model to test novel therapies.